Pembinaan Karakter Kepemimpinan Generasi Muda Melalui Organisasi Karang Taruna di Desa Banjarpanji Kecamatan Tanggulangin Kabupaten Sidoarjo - Nadiyah Anggun Eka Wardani; Wahyu Eko Pujianto (JURNAL RISET MANAJEMEN (JURMA), 2024)
The aim of this research is to analyze the existence of organizational The aim of this research is to analyze the influence of developing the leadership character of the second generation through the organization. The objects of this research are youth organizations in Banjarpanji Village, Tanggulangin District, Sidoarjo Regency. The qualitative approach is used as a research method, and uses a type of qualitative descriptive research which involves information in the form of written and spoken words based on objects that have been observed. The results of this research include the village's ability to provide guidance to youth which is very necessary to increase the leadership and organizational potential of youth. This is very appropriate if the implications are implemented through the Karang Taruna organization as a very secure forum for young people. Apart from that, existing theories can also be adapted to field conditions. Basically, balanced collaboration will create sustainable positive forces that can help and have an impact on the entire development of village communities, through the role of the young generation. The younger generation will also be the next generation for the surrounding community to lead and bring about change.